Malthus in Pre-industrial Northern Italy? A Cointegration Approach - Maja Pedersen; Claudia Riani; Paul Sharp (European Historical Economics Society (EHES), 2019)
Although a number of studies have attempted to test the hypothesis of a "Malthusian" pre-industrial world, few have focused on countries outside the UK, or on the "post-Malthusian" regime postulated by Unified Growth Theory. The present work is the first to test explicitly for the post-Malthusian regime in a setting outside the UK and Scandinavia, namely northern Italy from 1650. Employing a cointegrated VAR model, we find evidence that this part of the world does not fit cleanly into the Malthusian or post-Malthusian worlds, suggesting room for an extension of the simple Malthusian model.
Keywords: J1; N33; O4; 330; Cointegration; Italy; Malthusian; post-Malthusian